Compact Representations of Markov Decision Processes and Their Application to Printer Management - Torres, João Vitor; Cozman, Fabio Gagliardi; Rodrigues, André (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2007)
Many planning problems can be framed as Markov decision processes (MDPs). In this paper we discuss situations where regularities in states and variables lead to compact MDPs, particularly when variables have many categories and strong interrelation. We develop techniques that generate optimal policies by exploiting regularities in MDPs. We illustrate these ideas with a real problem on management of printing clusters.